Evaluación de los resultados de la ley de remisión sobre obligaciones tributarias contenidas en actos administrativos impugnados judicialmente: provincia del Guayas - Zambrano Aveiga, María Mercedes (2016)
In this paper, we intend to evaluate the results of Ley de Remisión de Intereses, Multas y Recargos, on revenue achieved in the province of Guayas, the obligations contained in administrative acts challenged in court. Likewise, the ways of extinguishing the tax liability, including referral as one described; other amnesty laws published in Latin America are analyzed: also refer to the single transitional provision of the Tax Equity Act that included the cancellation of interest, penalties and surcharges in 2008. Lastly is the number of lawsuits filed is pointed consequently of release, and the nominal increase in revenue in the province of Guayas.